Regio- and stereoselective synthesis of new ensembles of diversely functionalized 1,3-thiaselenol-2-ylmethyl selenides by a double rearrangement reaction - Amosova, Svetlana V.; Filippov, Andrey A.; Makhaeva, Nataliya A.; Albanov, Alexander I.; Potapov, Vladimir A. (Beilstein Journal of Organic Chemistry, 2020)
The reaction of 2-(bromomethyl)-1,3-thiaselenole with potassium selenocyanate proceeded via a rearrangement with ring expansion, leading to a six-membered 2,3-dihydro-1,4-thiaselenin-2-yl selenocyanate (kinetic product) which in turn underwent rearrangement with ring contraction to a 1,3-thiaselenol-2-ylmethyl selenocyanate (thermodynamic product). These rearrangements occurred by a nucleophilic attack of the selenocyanate anion at two different carbon atoms of the seleniranium intermediate. The efficient regioselective synthesis of alkyl, allyl, 2-propynyl, benzyl, 4-fluorobenzyl, and 2-pyridinylmethyl 1,3-thiaselenol-2-ylmethyl selenides was developed based on the generation of sodium 1,3-thiaselenol-2-ylmethylselenolate from 1,3-thiaselenol-2-ylmethyl selenocyanate or bis(1,3-thiaselenol-2-ylmethyl) diselenide followed by nucleophilic substitution reactions. Sodium 1,3-thiaselenol-2-ylmethylselenolate underwent nucleophilic addition to alkyl propiolates in a regio- and stereoselective manner affording 1,3-thiaselenol-2-ylmethyl vinyl selenides in high yields predominantly with Z-configuration. Not a single representative of the 1,3-thiaselenol-2-ylmethyl selenide scaffold has been previously described in the literature.
Keywords: 2-(bromomethyl)-1,3-thiaselenole; nucleophilic addition; nucleophilic substitution; rearrangement; seleniranium intermediate

(untitled) - Singh, F. V.; Wirth, T. (Phys. Sci. Rev., 2018)

(untitled) - Chivers, T.; Laitinen, R. S. (Phys. Sci. Rev., 2018)

New Selenium and Tellurium Chemistry. From Small Molecules to Biomolecules and Materials - Freudendahl, D. M.; Wirth, T. (New Selenium Electrophiles and Their Reactivity, 2011)

New Selenium and Tellurium Chemistry. From Small Molecules to Biomolecules and Materials - Dutton, J. L.; Ragogna, P. J. (Recent Developments in the Lewis Acidic Chemistry of Selenium and Tellurium Halides and Pseudo-Halides, 2011)

(untitled) - Denmark, S. E.; Collins, W. R.; Cullen, M. D. (J. Am. Chem. Soc., 2009)

(untitled) - Gabriele, E.; Singh, F. V.; Freudendahl, D. M.; Wirth, T. (Tetrahedron, 2012)

(untitled) - Singh, F. V.; Wirth, T. (Org. Lett., 2011)

(untitled) - Freudendahl, D. M.; Iwaoka, M.; Wirth, T. (Eur. J. Org. Chem., 2010)

(untitled) - Potapov, V. A.; Ishigeev, R. S.; Amosova, S. V.; Borodina, T. N. (Tetrahedron Lett., 2019)

Organoselenium Chemistry: Between Synthesis and Biochemistry - Ścianowski, J.; Rafiński, Z. (Electrophilic Selenium Reagents: Addition Reactions to Double Bonds and Selenocyclizations, 2014)

New Frontiers in Organoselenium Compounds - Lenardão, E. J.; Santi, C.; Sancineto, L. (Springer International Publishing AG, 2018)

(untitled) - Potapov, V. A.; Musalov, M. V.; Musalova, M. V.; Amosova, S. V. (Curr. Org. Chem., 2016)

(untitled) - Abakumov, G. A.; Piskunov, A. V.; Cherkasov, V. K.; Fedushkin, I. L.; Ananikov, V. P.; Eremin, D. B.; Gordeev, E. G.; Beletskaya, I. P.; Averin, A. D.; Bochkarev, M. N.; Trifonov, A. A.; Dzhemilev, U. M.; et al. (Russ. Chem. Rev., 2018)
Usp. Khim. 2018, 87, 393–507.

(untitled) - Potapov, V. A.; Amosova, S. V.; Belozerova, O. V.; Albanov, A. I.; Yarosh, O. G.; Voronkov, G. M. (Chem. Heterocycl. Compd., 2003)
Khim. Geterotsikl. Soed. 2003, 39, 633–634.

(untitled) - Potapov, V. A.; Amosova, S. V. (Russ. J. Org. Chem., 2003)
Zhurn. Org. Khim. 2003, 39, 1449-1455.

(untitled) - Lippolis, V.; Santi, C. (New J. Chem., 2019)

(untitled) - Nogueira, C. W.; Zeni, G.; Rocha, J. B. T. (Chem. Rev., 2004)

(untitled) - Banerjee, B.; Koketsu, M. (Coord. Chem. Rev., 2017)

(untitled) - Yoshida, S.; Kumakura, F.; Komatsu, I.; Arai, K.; Onuma, Y.; Hojo, H.; Singh, B. G.; Priyadarsini, K. I.; Iwaoka, M. (Angew. Chem., Int. Ed., 2011)

(untitled) - Kumakura, F.; Mishra, B.; Priyadarsini, K. I.; Iwaoka, M. (Eur. J. Org. Chem., 2010)

(untitled) - Tanini, D.; Lupori, B.; Malevolti, G.; Ambrosi, M.; Lo Nostro, P.; Capperucci, A. (Chem. Commun., 2019)

(untitled) - Tanini, D.; Degl'Innocenti, A.; Capperucci, A. (Eur. J. Org. Chem., 2015)

(untitled) - Borges, E. L.; Peglow, T. J.; Silva, M. S.; Jacoby, C. G.; Schneider, P. H.; Lenardão, E. J.; Jacob, R. G.; Perin, G. (New J. Chem., 2016)

(untitled) - Perin, G.; Alves, D.; Jacob, R. G.; Barcellos, A. M.; Soares, L. K.; Lenardão, E. J. (ChemistrySelect, 2016)

(untitled) - Tanini, D.; Scarpelli, S.; Ermini, E.; Capperucci, A. (Adv. Synth. Catal., 2019)

(untitled) - Tanini, D.; Tiberi, C.; Gellini, C.; Salvi, P. R.; Capperucci, A. (Adv. Synth. Catal., 2018)

(untitled) - Perin, G.; Lenardão, E. J.; Jacob, R. G.; Panatieri, R. B. (Chem. Rev., 2009)

(untitled) - Sun, K.; Shi, Z.; Liu, Z.; Luan, B.; Zhu, J.; Xue, Y. (Org. Lett., 2018)

(untitled) - Amosova, S. V.; Penzik, M. V.; Albanov, A. I.; Potapov, V. A. (Tetrahedron Lett., 2009)

(untitled) - Amosova, S. V.; Penzik, M. V.; Potapov, V. A.; Filippov, A. S.; Shagun, V. A.; Albanov, A. I.; Borodina, T. N.; Smirnov, V. I. (Synlett, 2016)

(untitled) - Amosova, S. V.; Novokshonova, I. A.; Penzik, M. V.; Filippov, A. S.; Albanov, A. I.; Potapov, V. A. (Tetrahedron Lett., 2017)

Divinyl Sulfide and Its Derivatives - Trofimov, B. A.; Amosova, S. V. (Nauka, 1983)

(untitled) - Trofimov, B. A.; Amosova, S. V. (Sulfur Rep., 1984)

(untitled) - Trofimov, B. A.; Amosova, S. V.; Gurasova, N. K.; Musorin, G. K. (Tetrahedron, 1982)

(untitled) - Accurso, A. A.; Cho, S.-H.; Amin, A.; Potapov, V. A.; Amosova, S. V.; Finn, M. G. (J. Org. Chem., 2011)

(untitled) - Penzik, M. V.; Amosova, S. V.; Albanov, A. I.; Potapov, V. A. (Russ. J. Org. Chem., 2014)
Zhurn. Org. Khim. 2014, 50, 930–932.

(untitled) - Amosova, S. V.; Filippov, A. S.; Potapov, V. A.; Penzik, M. V.; Makhaeva, N. A.; Albanov, A. I. (Synthesis, 2019)

(untitled) - Amosova, S. V.; Filippov, A. S.; Potapov, V. A.; Penzik, M. V.; Albanov, A. I. (Russ. J. Org. Chem., 2017)
Zhurn. Org. Khim. 2017, 53, 1842–1844.

(untitled) - Amosova, S. V.; Filippov, A. S.; Makhaeva, N. A.; Albanov, A. I.; Potapov, V. A. (New J. Chem., 2019)

(untitled) - Amosova, S. V.; Rykunova, Y. I.; Filippov, A. S.; Penzik, M. V.; Makhaeva, N. A.; Albanov, A. I.; Potapov, V. A. (J. Organomet. Chem., 2018)

(untitled) - Amosova, S. V.; Penzik, M. V.; Potapov, V. A.; Albanov, A. I. (Russ. Chem. Bull., 2011)
Izv. AN Ser. Khim. 2011, 750.

(untitled) - Amosova, S. V.; Penzik, M. V.; Filippov, A. S.; Albanov, A. I.; Potapov, V. A. (Russ. J. Org. Chem., 2014)
Zhurn. Org. Khim. 2014, 50, 1718–1720.

(untitled) - Amosova, S. V.; Penzik, M. V.; Potapov, V. A.; Albanov, A. I. (Russ. J. Org. Chem., 2014)
Zhurn. Org. Khim. 2012, 48, 1519-1520.

(untitled) - Amosova, S. V.; Penzik, M. V.; Rykunova, Yu. I.; Potapov, V. A.; Albanov, A. I. (Russ. J. Org. Chem., 2017)
Zhurn. Org. Khim. 2017, 53, 1655–1658.

(untitled) - Amosova, S. V.; Penzik, M. V.; Potapov, V. A.; Albanov, A. I. (Russ. J. Org. Chem., 2015)
Zhurn. Org. Khim. 2015, 51, 297–299.

(untitled) - Potapov, V. A.; Filippov, A. S.; Amosova, S. V. (Russ. J. Org. Chem., 2018)
Zhurn. Org. Khim. 2018, 54, 949–950.